Penerapan Model Integrated Curriculum di SMP Muhammadiyah Plus Klaten - Sukron Sa’id; Suyatno Suyatno; Sukirman Sukirman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The dichotomy of knowledge between general science and religious knowledge causes alumni at Islamic educational institutions to experience split personalities. Therefore, it is necessary to develop a curriculum that integrates general science and religious knowledge as a whole. This study examines the implementation of the integrated curriculum at SMP Muhammadiyah Plus Klaten. Using a qualitative approach with a case study design, the research identifies how an integrated curriculum can unify the national curriculum, the Ministry of Religious Affairs curriculum, and the pesantren curriculum. Data was collected through interviews, observation and documentation. Data were analyzed using the Miles & Huberman model of interactive inductive data analysis techniques. The research results show that the implementation of the integrated curriculum includes integration of aspects of objectives, materials, methods and learning evaluation. The integration of these four aspects of the curriculum seeks to improve the quality of education and form holistic and integrative personalities in students. Despite challenges such as integrating different disciplines, these are mitigated through teacher training and collaboration with parents. The results offer a potential framework for other educational institutions to implement integrated curricula.